Integrating LCA and Carbon Accounting for Gate-to-Gate Sustainability Improvement: Evidence from Liquid Nitrogen Injection in KBR Purifier Unit for Liquid Ammonia Production - Kurniawan, Muhammad Prasetya; Wijaya, Hanung; Huda, Khoirul; Anggraini, Ananda Dian; Larasati, Errika Anggraini; Nurramdhana, Almaira Daffa (Jurnal Ilmiah Inovasi, 2025)
This research combines Life Cycle Assessment (LCA) and Carbon Accounting to quantify sustainability performance improvements in ammonia production. Emphasis is placed on gate-to-gate in the start-up phase of the purifier unit where energy use is high. Typically, start up in ammonia plants is a 20-25 hour long process that consumes large volumes of natural gas and steam resulting in substantial carbon emissions and inefficiency. This statement presents the technology of LIN (Liquid Nitrogen) Injection, which is used to accelerate the cooling process of purifier units at a temperature between −100 to−186 °C, reduces star-up duration by an estimation about 10.56 hours. ISO 14064-1 and SNI 7724:2011 standards were used, a gaseous mass, energy, and emission balance was carried out. Results also indicate that LIN Injection reduces natural gas consumption of 10.92 tons, steam with a factor of 899.56 tons and total energy Mech/ηµ using start-up cycle 592.89 GJ. This is equivalent to 33.3-34.2 tons of CO₂e emission reduction. This process-oriented decarbonization supports the MRV system, which enables carbon credit registration according to Indonesian’s IDX Carbon market framework.